Assessing the evidence–practice gap for heart failure in China: the Heart Failure Registry of Patient Outcomes (HERO) study design and baseline characteristics. (9th December 2019) - Li, Li; Liu, Rong; Jiang, Chao; Du, Xin; Huffman, Mark D.; Lam, Carolyn S.P.; Patel, Anushka; Hillis, Graham S.; Anderson, Craig S.; Ma, Changsheng; Zhao, Xiaoyan; Wang, Xiaofang; et al.
Abstract: Background: Registry studies in high‐income countries have defined contemporary management of heart failure (HF), but few such data exist in the large aging population of China. We report the study design and baseline characteristics of the Heart Failure Registry of Patient Outcomes (HERO) study, undertaken to determine evidence–practice gaps in the management of HF in a broad and representative population of China. Methods and results: The HERO study is a prospective, longitudinal, seasonally‐rotating, multicentre registry study of patients hospitalized with acute HF who are followed up over 12 months. Patients were recruited on the basis of primary admission clinical diagnosis of acute HF at 73 hospitals in Henan, the largest and most socio‐economically diverse province in China, from November 2017 to November 2018; follow‐up is ongoing. For each patient, data obtained through interview and medial record review by independent clinical research staff include: socio‐demographics, clinical features, diagnostic investigations, and treatment, with a subset of patients providing blood samples for future biomarker investigation. Surviving patients are scheduled to be followed up by telephone at 2 weeks, and 3, 6 and 12 months post‐admission, or until death or study withdrawal. A total of 5620 patients (mean age 72 ± 12 years; 50% female) with acute HF were recruited from 8 provincial‐, 22 municipal‐, and 43 county‐level hospitals. Patients had co‐morbid hypertensive (48%), coronary (29%), or metabolic (20%) diseases. Among 3147 patients who had echocardiography, 54%, 20% and 25% of patients had ejection fraction of ≥50%, 40–50%, and < 40%, respectively. In‐hospital or 3‐day post‐discharge mortality was 3.2% (182/5620). Death or readmission rate from the 4th day post‐discharge to first follow‐up (median 32 days) was 22.4% (977/4368). Conclusions: The HERO study provides a unique opportunity to profile evidence–practice gaps across a broad spectrum of patients with acute HF in China.